Cognitively‐Based Compassion Training for parents reduces cortisol in infants and young children. Issue 1 (4th October 2019) - Poehlmann‐Tynan, Julie; Engbretson, Ashleigh; Vigna, Abra B.; Weymouth, Lindsay A.; Burnson, Cynthia; Zahn‐Waxler, Carolyn; Kapoor, Amita; Gerstein, Emily D.; Fanning, Kerrie A.; Raison, Charles L.
ABSTRACT: This study tests a group‐based secular contemplative practice intervention, Cognitively‐Based Compassion Training (CBCT), with parents of young children. We report on a randomized controlled preliminary efficacy study. Certified teachers administered CBCT for 20 hr across 8 to 10 weeks in two cohorts of parents with infants and young children. The intervention group was compared to a waitlist control group. Thirty‐nine parents and their children, who ranged in age from 4 months to 5 years, were evaluated at pre‐ and postintervention ( n = 25 intervention, n = 14 waitlist control) on hair cortisol concentration. Parents also completed self‐administered questionnaires at both time points regarding demographics, physical symptoms of stress, parenting stress, self‐compassion, and mindfulness. Children of parents in the CBCT group experienced significant decreases in cortisol at the postintervention assessment, as compared with the control group. However, parent cortisol and self‐report measures did not significantly change other than a small effect on clinical levels of parenting stress. CBCT may be a positive new way to intervene with parents to lower infants' and young children's cumulative physiological stress. RESUMEN: Este estudio puso a prueba una práctica de intervención contemplativa secular con base en un grupo, el Entrenamiento Compasivo con Base Cognitiva (CBCT), con padres de niños pequeños. Nosotros reportamos sobre un estudio de efectividad preliminar controlado al azar. Maestros titulados administraron el CBCT por 20 horas a lo largo de 8‐10 semanas en dos grupos de padres con infantes y niños pequeños. El grupo de intervención fue comparado con un grupo de control en lista de espera. Treinta y nueve padres y sus niños, que oscilaban en edad de 4 meses a 5 años, fueron evaluados antes y después de la intervención (n=25 grupo de intervención, n=14 grupo de control en lista de espera) en cuanto a la concentración de cortisol en el cabello. Los padres también completaron cuestionarios auto‐administrados en ambos momentos temporales con respecto a información demográfica, síntomas físicos de estrés, estrés de crianza, auto‐compasión, así como plena conciencia. Los niños de padres en el grupo CBCT experimentaron una significativa disminución de cortisol al momento de la evaluación posterior a la intervención, tal como se les comparó con el grupo de control. Sin embargo, el cortisol de los padres y las medidas de auto‐reporte no cambiaron significativamente. El CBCT pudiera ser una nueva manera positiva de intervenir con padres para reducir el estrés fisiológico cumulativo de infantes y niños pequeños. RÉSUMÉ: Cette étude a testé une intervention de pratique contemplative séculaire et basée sur un groupe, la Formation de Compassion Cognitive (abrégé ici selon l'anglais CBCT), avec des parents de jeunes enfants. Cet article porte sur une étude d'efficacité préliminaire randomisée et contrôlée. Des formateurs certifiés ont procédé à une CBCT de 20 heures réparties sur 8‐10 semaines chez deux cohortes de parents avec des nourrissons et des jeunes enfants. Le groupe d'intervention a été comparé à un groupe de contrôle en liste d'attente. Trente‐neuf parents et leurs enfants, allant de 4 mois à 5 ans d'âge, ont été évalués avant et après l'intervention (n=25 intervention, n=14 contrôle de liste d'attente) sur la concentration de cortisol capillaire. Les parents ont également rempli des questionnaires auto‐administrés aux deux temps d'évaluation, concernant des données démographiques, les symptômes physiques de stress, le stress de parentage, l'auto‐compassion et la pleine conscience. Les enfants de parents du groupe CBCT ont fait preuve de baisses de niveau de cortisol importantes à l'évaluation post‐intervention en comparaison au groupe de contrôle. Cependant le cortisol parental et les mesures auto‐rapportées n'ont pas changé de manière importante. La CBCT peut être une nouvelle manière positive d'intervenir avec les parents afin de faire baisser le stress physiologique cumulatif des nourrissons et des jeunes enfants. ZUSAMMENFASSUNG: Kognitiv‐basiertes Mitgefühlstraining (CBCT) für Eltern reduziert Cortisol bei Säuglingen und Kleinkindern Die vorliegende Studie testet eine gruppenbasierte säkulare kontemplative Praxisintervention, das Kognitiv‐basiertes Mitgefühlstraining (Cognitive‐Based Compassion Training; CBCT), mit Eltern kleiner Kinder. Es handelt sich hierbei um eine randomisierte kontrollierte vorläufige Wirksamkeitsstudie. Zertifizierte Lehrkräfte führten das CBCT über einen Zeitraum von 20 Stunden in 8 bis 10 Wochen mit 2 Kohorten von Eltern mit Säuglingen und Kleinkindern aus. Die Interventionsgruppe wurde mit einer Wartelisten‐Kontrollgruppe verglichen. 39 Eltern und ihre Kinder im Alter von 4 Monaten bis 5 Jahren wurden vor und nach der Intervention hinsichtlich der Cortisolkonzentration in ihren Haaren untersucht (n = 25 Interventionsgruppe, n = 14 Wartelistengruppe). Die Eltern füllten zu beiden Zeitpunkten zudem selbstverantwortlich Fragebögen zu demografischen Angaben, körperlichen Stresssymptomen, Erziehungsstress, Selbstmitgefühl und Achtsamkeit aus. Bei Kindern der Eltern in der CBCT‐Gruppe war bei der Beurteilung nach der Intervention im Vergleich zur Kontrollgruppe ein signifikanter Rückgang des Cortisols zu verzeichnen. Die elterlichen Cortisolwerte und Selbstberichtsmaße änderten sich jedoch nicht signifikant. Das CBCT könnte eine positive neue Möglichkeit sein, bei Eltern einzugreifen, um den kumulativen physiologischen Stress von Säuglingen und Kleinkindern zu senken. 抄録: 両親に行った認知に基づく共感トレーニング (Cognitively‐Based Compassion Training: CBCT) による乳児や幼児のコルチゾールの減少 本研究では、幼児を持つ両親に対しグループでの非宗教的な瞑想的実践介入 (group‐based secular contemplative practice intervention)、認知に基づく共感トレーニング (Cognitively‐Based Compassion Training: CBCT) を実施した。われわれが行った予備的な無作為化比較試験の効果研究について報告する。資格を持つ教員が乳児や幼児を持つ両親の二つのグループに対し、8～10 週間にわたって 20 時間の CBCT を行った。介入グループと非介入コントロールグループを比較した。 39 組の両親とその 4 か月 ～5 歳の年齢の子どもについて、介入前後 (介入グループ n = 25、非介入グループ n = 14) の時点で頭髪中のコルチゾールを評価した。両親には、介入前後の時点で統計上のデータ、ストレスによる身体症状、子育てのストレス、セルフ・コンパッション (self‐compassion)、そしてマインドフルネス (mindfulness) に関する自記式質問紙を記入してもらった。介入後の評価時点において、CBCT (介入) グループの両親の子どもではコントロール (非介入) グループの子どもに比べ、コルチゾールが有意に減少していた。しかしながら、両親のコルチゾールや自記式評価尺度では、有意な変化は認められなかった。 CBCT は、乳児や幼児の累積的な身体的ストレスを軽減するために役立つ、新しい介入法になるかも知れない。 摘要: 父母基於認知的同情訓練)CBCT(減少嬰兒和幼兒的皮質醇 本研究測試一個對幼兒父母長期沉思實踐干預小組, 即基於認知的同情訓練 (CBCT)。我們報告一項隨機對照組的初步療效研究。經過認證的教師在兩個同齡群嬰兒的父母中進行 8–10 週的 20 小時 CBCT 培訓。研究比較干預組與候補名單對照組。在干預前和干預後 (n = 25 干預組, n = 14 候補名單對照組), 對年齡在 4 個月至 5 歲之間的 39 位父母及其子女作出頭髮皮質醇的濃度評估。父母還在兩個時間點完成有關其特徵丶壓力的生理症狀丶育兒壓力丶自我同情和內觀的問卷。與對照組相比, CBCT 組父母的孩子在干預後皮質醇顯著下降。但是, 父母的皮質醇和自我報告並沒有明顯改變。 CBCT 可能是一種積極干預父母的新方法, 可以降低嬰兒和幼兒的累積生理壓力。 ملخص: تدريب التعاطف القائم علي المعرفة (CBCT) للوالدين يقلل من الكورتيزول في الرضع والأطفال الصغار تتناول هذه الدراسة التدخل التاملي القائم علي المجموعة ، والتدريب علي التعاطف المعرفي (CBCT) ، مع آباء وأمهات الأطفال الصغار. وتقدم تقريرا عن دراسة مبدأية منضبطة تجريبيا للكفاءة الأولية. قام مدرسون مؤهلون ومعتمدون بإدارة تدريب العاطفة المعرفية CBCT لمده 20 ساعة خلال 8‐10 أسابيع مع مجموعتين من الاباء والأمهات الذين لديهم رضع وأطفال الصغار. تمت مقارنه مجموعه التدخل بالمجموعة الضابطة في قائمه الانتظار. وتم تقييم مجموعة من 39 من الاباء والأمهات وأطفالهم ، الذين تراوحوا في العمر من 4 أشهر إلى 5 سنوات ، في مرحله ما قبل وبعد التدخل (n = 25 المجموعة التجريبية ، n = 14 المجموعة الضابطة) من حيث تركيز الكورتيزول في الشعر. واستكمل الاباء أيضا الاستبيانات التي تدار ذاتيا في كلا التوقيتين فيما يتعلق بالديموغرافيات ، والاعراض الجسدية للإجهاد ، وإجهاد الرعاية الولدية ، والتعاطف الذاتي ، واليقظة. وقد أظهر أطفال الاباء في مجموعه CBCT انخفاضات كبيره في الكورتيزول في تقييم ما بعد التدخل مقارنه بالمجموعة. ومع ذلك ، فإن الكورتيزول عند الوالدين ومقاييس التقرير الذاتي لم تتغير بشكل كبير. وبذلك قد يكون CBCT طريقه ايجابيه جديده للتدخل مع الاباء لخفض الإجهاد الفسيولوجي التراكمي للرضع والأطفال الصغار.